Understanding Business Intelligence and Analytics System Success from Various Business Sectors in Indonesia - Sevenpri Candra; Ambi Nainggolan (Bina Nusantara University, 2022)
Many studies have shown the impact of the Business Intelligence and Analytics (BI&A) system on decision-making. Many organizations have invested heavily in BI technology and the growth of analytical skills and made the BI&A system a strategic priority over the last eight years by citing it as the largest IT investment. The research aims to determine the relevant constructs contributing to the organization’s BI&A system success. Survey research is applied to collect quantitative data for the research questions. The questionnaire is developed in English, which is translated into bahasa Indonesia later. The research obtains 208 decision-makers who use and utilize the BI&A system in various business sectors in Indonesia to achieve this goal. Then, PLS-SEM is used for measurement validation and hypothesis testing. About 8 out of 11 hypothesized relationships between 7 success factors are significantly supported. The findings demonstrate that the model constructs significantly improve decision-making quality in the BI&A system environment. Service quality is found to be the highest predictor of system use. Meanwhile, information quality is the highest predictor of user satisfaction. The research presents practical implications for organizations to adopt the essential factors of BI&A system finding to realize organizational success. Moreover, organizations that have already implemented the BI&A system can use the research as a theoretical basis to measure the ability of the BI&A system to improve decision-making quality.